2016
DOI: 10.1002/jbmr.2899
|View full text |Cite
|
Sign up to set email alerts
|

WNT5A and Its Receptors in the Bone-Cancer Dialogue

Abstract: Wnt signaling is critical for tumorigenesis and skeletal remodeling. However, its contribution to the formation of metastatic bone lesions remains poorly defined. One major challenge of unraveling its role in cancer progression is the high complexity of Wnt signaling, which includes numerous ligands, receptors, and inhibitors, with intricate biological effects and specific signaling pathways depending on the cellular context. In this perspective, we summarize the role of the noncanonical Wnt ligand WNT5A in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 134 publications
0
8
0
Order By: Relevance
“…We found that cells of cancer 4 cluster had high-level expression of FZD1 which interacted with the receptor WNT5A of monocytes (Fig. 3I, J), and the ligand-receptor complex of FZD1/WNT5A played a key role in cancer cells by promoting the proliferation and differentiation of monocytes into osteoclasts [36] ( Fig. 3I, J).…”
Section: Identification Of the Potential Evolution Process In The Bonmentioning
confidence: 91%
“…We found that cells of cancer 4 cluster had high-level expression of FZD1 which interacted with the receptor WNT5A of monocytes (Fig. 3I, J), and the ligand-receptor complex of FZD1/WNT5A played a key role in cancer cells by promoting the proliferation and differentiation of monocytes into osteoclasts [36] ( Fig. 3I, J).…”
Section: Identification Of the Potential Evolution Process In The Bonmentioning
confidence: 91%
“…Furthermore, there is an abundant release of TGF-β and vascular endothelial growth factor (VEGF) by the cancer cells, which directly affect the osteoblast activity [ 45 ]. This is done through the WNT pathway, which is implicated in osteoblastogenesis [ 46 , 47 , 48 ]. The combination of this WNT pathway upregulation coupled with the reported decreased expression of the WNT antagonist, dikkopf-1, in patients with advanced prostate cancer is associated with the formation of osteoblastic lesions ( Figure 1 b) [ 49 ].…”
Section: Biology Of Bone Metastasismentioning
confidence: 99%
“…Recent studies identified WNT5A to interact with various members of the FZD family (FZD2, 3, 4, 7, 8) as well as the co-receptors ROR2 and RYK [ 7 ]. Moreover, WNT5A and its receptors have been implicated in different human cancer entities including glioblastoma, leukemia, and pancreatic cancer [ 17 23 ]. After having previously shown that WNT5A exerts potent anti-tumor effects in prostate cancer cells [ 5 ], this study aimed to investigate which of the receptors mediates its anti-tumor effects.…”
Section: Introductionmentioning
confidence: 99%